Applications in bioinformatics with Markov models - Robinson, Sean (fi=Turun yliopisto|en=University of Turku|, 2018)
In this thesis we present four applications in bioinformatics with Markov models. That is, we extend the use of such models in the mathematical and statistical analysis of biological data. The data we consider are drawn from a broad range of areas. We consider applications at the genomic level with time series and network data as well as applications at the cellular level with microscopy image data of both cell culture and in vivo tissue. Collections of objects such as genes, cells or pixels are of particular interest as a whole. We make use of associations within these collections, spatial, temporal or functional, and assume that closer objects are more strongly associated than those further apart. This allows for efficient inference within a Markov model framework and is encoded in terms of conditional independences between variables as represented by vertices and edges in an undirected graph. Chapter 1 presents an overview of undirected graphical models in general and Markov models in particular. Chapter 2 presents inference for variables in hidden Markov random fields (MRFs) while Chapter 3 presents inference for the parameters of Gaussian MRFs. Chapter 4 outlines the four applications and how the Markov model framework is utilised in each case. For each application, the associated publication is also provided. In Publication 1, hidden Markov models (HMMs) are used to achieve an alignment and classification of time series data. Publications 2 and 3 concern inference with hidden MRFs to obtain a segmentation of both digital image data and network data respectively. Spatial analysis with Gaussian MRFs is presented in Publication 4. We show that our particular use of Markov models in each of our applications enables us to achieve our aims.

Dans cette thèse nous présentons quatre applications en bioinformatique avec des modèles de Markov. Plus précisément, nous étendons ces modèles à l’analyse statistique et mathématique de données biologiques. Les données que nous étudions viennent de différentes sources. Nous considérons les applications au niveau génomique avec des séries temporelles et des données de réseau ainsi que les applications au niveau cellulaire avec des données d’images de microscopie de cultures cellulaires et de tissus in vivo. Les ensembles d’objets tels que gènes, cellules ou pixels, présentent un intérêt dans leur intégralité. Nous utilisons des associations spatiales, temporelles ou fonctionnelles au sein de ces ensembles et nous supposons que les objets qui sont plus proches les uns des autres sont plus fortement liés que ceux qui sont plus éloignés. Cela permet une inférence efficace dans le cadre des modèles de Markov et est codé par des indépendances conditionnelles entre variables qui sont représentées par des sommets et arêtes dans un graphe non orienté. Le chapitre 1 présente une vue d’ensemble des modèles graphiques non orientés en général et des modèles de Markov en particulier. Le chapitre 2 présente l’inférence des variables des champs aléatoires de Markov (MRFs) cachés tandis que le chapitre 3 présente l’inférence des paramètres des MRFs de Gauss. Le chapitre 4 expose les quatre applications traitées et comment le cadre des modèles de Markov est utilisé dans chaque cas. Pour chacune des applications, la publication associée est fournie. Dans la publication 1, les modèles de Markov cachés (HMMs) sont utilisés pour atteindre un alignement et une classification des données de séries temporelles. Les publications 2 et 3 concernent l’inférence à la fois avec des MRFs cachés pour obtenir une segmentation des données d’images numériques et des données de réseau. Une analyse spatiale avec des MRFs de Gauss est présentée dans la publication 4. Nous montrons que notre utilisation particulière des modèles de Markov dans chaque publication nous a permis d’atteindre nos objectifs.